2016
DOI: 10.5505/jems.2016.05706
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Maritime piracy and Armed Robbery in the Gulf of Guinea Maritime Domain

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The works of [20][21][22][23] supports the position of the Frustration-Aggression Theory (FAT), in which human frustration may lead to aggressive behavior and/or violence. Reference [11] agrees that frustration ultimately leads to aggression, and aggression always implies that frustration has occurred at some previous time.…”
Section: Introductionmentioning
confidence: 94%
“…The works of [20][21][22][23] supports the position of the Frustration-Aggression Theory (FAT), in which human frustration may lead to aggressive behavior and/or violence. Reference [11] agrees that frustration ultimately leads to aggression, and aggression always implies that frustration has occurred at some previous time.…”
Section: Introductionmentioning
confidence: 94%
“…This study observed that the African seaways namely; the coast of the Horn of Africa (HOA) and the Gulf of Aden (GOA); in the East coast of Africa, and the Gulf of Guinea (GOG); in the West coast of Africa dominated by Nigeria in terms of ships and cargo movement, from the year 1999 to date have become mine fields for sea pirates, witnessing intense attacks against ships. [31][32][33][34][35] This threatens maritime security in the zones affecting negatively global trade flows and economic growth in Nigeria. Since 2007, African waters overtook waters off Southeast Asia of Indonesia, Malaysia, and Singapore; of global maritime piracy with much of the global attention in African waters being on Nigeria maritime piracy as a result of the growing presence of the militancy in the area.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Studies by Nnadi, et al (2016) note that maritime piracy and sea robbery attacks against ships constitute major threats to maritime security in global waters. Maritime piracy and sea robbery attacks against ships trading in West African waters particularly in the coast of Nigeria over the past two decades has continued unabated, worsening the insecurity challenges in the Gulf of Guinea maritime region.…”
Section: Introductionmentioning
confidence: 99%
“…It further defines piracy as any act of inciting or of intentionally facilitating an act aimed at forcefully boarding a ship with apparent intent to commit illegal acts of violence or detention, or any act of depression, committed for purposes of private ends by the crew or passengers of a pirate boat or aircraft in the high seas (Eregha & Irughe, 2009). Thus, many scholars agreed that attacks against ships trading in global waters and territorial sea has far reaching influence on maritime operations, productivity of maritime organizations and socio economic implications on the general society and standard of living (Nnadi et al, 2016;Onuoha, 2012;Beardsly, 2014). Studies by Essien and Adongoi (2015) observed the prevalent incidence of pirate attacks against ships involved in trade in the in coastal communities in the Gulf of Guinea maritime domain threatens maritime security in the zones; affecting negatively global trade flows and economic growth in West Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation